Carboxylate-Containing Two-Photon Probe for the Simultaneous Detection of Extra- and Intracellular pH Values in Colon Cancer Tissue - Si, Ho Young; Cho, Myoung Ki; Kang, Ji Su; Noh, Choong Kyun; Shin, Sung Jae; Lim, Chang Su; Kim, Hwan Myung (Analytical Chemistry, 2018)
Acidified extracellular pH (pHe) is directly related to various disorders such as tumor invasion and the resistance to drugs. In this study, we developed two-photon-excitable emission ratiometric probes (XBH1-3) for the in situ measurement of pHe. These probes, based on benzimidazole and polar solubilizing groups, exhibited a strong two-photon-induced fluorescence and sensitive blue-to-green emission color changes with pKa values of 5.1-5.7. XBH1, containing a carboxylic acid, stained the extracellular region in neutral media; it entered the cell under acidic media, thereby allowing a precise measurement of the extra- and intra-cellular pH values in the acidified tissue. XBH2, containing the sulfonate peripheral unit, facilitated the monitoring of the pHe value only. Ratiometric two-photon microscopy imaging revealed that XBH1 can directly monitor the pH values both inside and outside the cells in colon cancer tissue; there is also the morphological aspect. This could be useful for cancer analyses and drug development.
Keywords: Extracellular region; In-situ measurement; Intracellular pH; Precise measurements; Simultaneous detection; Two photon microscopy; Two-photon excited fluorescence; Two-photon probes; Carboxylic Acids; Cell Line, Tumor; Colonic Neoplasms; Extracellular Space; Fluorescent Dyes; HeLa Cells; Humans; Hydrogen-Ion Concentration; Intracellular Space; Photons; Solubility; Spectrometry, Fluorescence; Sulfonic Acids; Time Factors